Impact of Investment, Financing, Dividend Policy, and Profitability Decisions on Firm Value in Banking Companies Listed on The Indonesia Stock Exchange for the Period 2019-2023 - Indah Sari Br Siagian; Laily Ramadhani; Raymond Fransiscus (Jurnal Visi Manajemen, 2025)
His study aims to investigate the influence of investment decisions, financing, dividend policy, and profitability on the firm value of State-Owned Enterprise (SOE) banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research is motivated by the fluctuating firm value (PBV), which reached a low of 1.66 in 2020 and a high of 2.05 in 2022, indicating shifts in market perception. Using a quantitative approach and a purposive sampling method, this study analyzes secondary data from four SOE banks: PT Bank Mandiri Tbk, PT Bank Rakyat Indonesia Tbk, PT Bank BNI Tbk, and PT Bank BTN Tbk. The data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression. The results show that investment decisions, dividend policy, and profitability have a significant positive effect on firm value. In contrast, financing decisions were found to have no significant effect on firm value. This study concludes that an integrated approach to financial management is essential for creating long-term firm value.